KLASYFIKACJA FORM KOMUNIKATÓW DYDAKTYCZNYCH - Kąkolewicz, Mariusz (Wydawnictwo Naukowe UAM w Poznaniu, 1996)
Kąkolewicz Mariusz, Klasyfikacja form komunikatów dydaktycznych (Classification of didactical message form), „Neodidagmata" XXII, Poznań 1996, Adam Mickiewicz University Press, pp. 139-147. ISBN 83-232-0710-0. ISSN 0077-653X. This article discusses the importance of the term form o f didactical message. Different meanings of the term form and its importance for thinking about educational tools and materials are presented. Multimedia computers (now with CD-ROM's) are thought to be a universal tool for presenting all possible forms of information: written, spoken, audial, visual and audio-visual, all interactive, of course. A proposal of division of different multimedia forms of information on the basis of the following categories: dimension, complexity, movement, registration, presenting, and interaction, is presented. The rapid development of information technology creates the need of a new approach to the division of educational tools on the basis of the form of didactical messages.
Keywords: Multimedia; Informacja; Komunikat; Komunikat dydaktyczny; Urządzenia techniczne; Information; Communicat; Information technology; Neodidagmata